Efficient and moisture-resistant organic solar cells via simultaneously reducing the surface defects and hydrophilicity of an electron transport layer. Issue 38 (10th September 2021) - Gao, Xueman; Su, Zhenhuang; Qu, Shengchun; Zhang, Wenzhi; Gao, Yueyue; He, Shenghua; Wang, Zhijie; Shang, Luwen; Dong, Guohua; Yue, Gentian; Tan, Furui; Wang, Zhangguo
Abstract : A novel low-cost TSi/ZnO bilayer electron transport layer was developed, which could simultaneously enhance the efficiency and device stability to moisture of derived OSCs. Abstract : Organic solar cells (OSCs) simultaneously featuring good photovoltaic performance and strong humidity resistance are greatly anticipated for their practical application. Herein, we developed a simple organic trisiloxane molecule (denoted as TSi), and applied it to modify sol–gel ZnO (sg-ZnO) films. Compared to pristine sg-ZnO films, the TSi/sg-ZnO film presents fewer surface defects, shallower work function, and stronger hydrophobicity. Benefiting from those improved characteristics, when adopting a benzodifuran (BDF)-based polymer (BDFP-Bz) and Y6 as the electron donor and acceptor to fabricate OSCs, the derived devices utilizing TSi/sg-ZnO as the electron transport layer (ETL) showed suppressed charge recombination, enhanced charge extraction and increased stability to moisture versus the devices based on an sg-ZnO ETL. Meanwhile, PBDFP-Bz:Y6 OSCs based on a TSi/sg-ZnO ETL delivered a higher PCE of 14.62% than that of the control devices (12.39%). More importantly, the TSi/sg-ZnO ETL was also applicable in other different photovoltaic systems, among which PM6:Y6 OSCs based on a TSi/sg-ZnO ETL yielded a superior PCE of 16.37% along with stronger stability to moisture versus the reference ones. Our finding demonstrates the TSi/sg-ZnO bilayer ETL holds promise in the practical application of OSCs for simultaneously improving the photovoltaic performance and moisture-resistance of devices.